Respuesta :

Answer:

Step-by-step explanation:

First, write down what we know. We have two equations and we need to find the solution.

y = 3x - 4

2y = 6x - 8

Notice that the second equation is twice the first equation.

To find the solution, we can use the y=y method, but first we need to simplify the second equation by dividing the equation by 2

2y = 6x - 8

y = 3x - 4

Next, find the solution:

3x - 4 = 3x -4

Since the equations are the same, there are infinite solutions, and when graphing, the lines will be in each other. Hope this helps, and Brainly will be highly appreciated.

ACCESS MORE